2007
DOI: 10.1089/vbz.2006.0576
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Wild Boar (Sus scrofa) in The Eco-epidemiology of R. slovaca in Northeastern Spain

Abstract: Rickettsia slovaca is considered the etiological agent of tick-borne lymphadenopathy (TIBOLA), an emerging disease transmitted by tick bites. Dermacentor marginatus constitutes the most important vector and wild boar (Sus scrofa) is the main wild host in our area. The epidemiology of this tick-borne rickettsioses has not been completely clarified. During hunting season 2004, wild boar sera sample were collected from northeastern Spain. Ticks were collected both from wild boar and from flagging vegetation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 23 publications
4
32
3
1
Order By: Relevance
“…It is interesting to note that the seroprevalence of R. slovaca in the bullfighting cattle was higher than in sheep and goats. In fact, seroprevalence in bullfighting cattle was similar to that obtained by our group in a previous study in wild boars (52.1%) (Ortuñ o et al 2007). It could be suggested that habitat may be an important factor to take into account, as sheep and goats live on grazing land that is not a proper habitat for D. marginatus.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is interesting to note that the seroprevalence of R. slovaca in the bullfighting cattle was higher than in sheep and goats. In fact, seroprevalence in bullfighting cattle was similar to that obtained by our group in a previous study in wild boars (52.1%) (Ortuñ o et al 2007). It could be suggested that habitat may be an important factor to take into account, as sheep and goats live on grazing land that is not a proper habitat for D. marginatus.…”
Section: Discussionsupporting
confidence: 90%
“…An earlier report showed the prevalence of R. slovaca infection in D. marginatus ticks captured from wild boars to be 30.5% (Ortuñ o et al 2007). Although serology is considered the easiest method for the detection of SFG rickettsiae, the interpretation of serological data is difficult because of the cross-reactivities among SFG when using IFA assays (Brouqui et al 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Local investigations showed that wild boars, which seem to be important in the epidemiology of R. slovaca (13), are found in this area. In the northern part of this area, woodland habitat and human habits increase the risk for human contact with vectors.…”
Section: Discussionmentioning
confidence: 93%
“…These authors suggested that these vertebrate hosts could play an important role as amplifier hosts of R. rickettsii for ticks in nature. With regard to other Rickettsia species, molecular and serological studies have suggested some potential animal reservoirs; however, further studies need to be performed to confirm these hypothesized reservoirs, such as cattle for R. africae (41), wild boars and domestic ruminants for Rickettsia slovaca (42,43), and sika deer for Rickettsia helvetica (44).…”
Section: Figmentioning
confidence: 99%